Architectural guide Oslo - Nielsen, Henning 1956-; Meyer, Ulf 1970- (DOM publishers, 2019)
Once known mainly for its natural surroundings, Oslo is now firmly on the map for its architecture. Contemporary showpieces such as Renzo Piano's Astrup Fearnley Museum, Snøhetta's iconic opera house, and the Barcode project line its new waterfront. This geographically organised guide leads the reader on a tour of these masterworks, as well as out to the regions around Scandinavia's smallest capital. It takes in everywhere from a brutalist church with an inverted dome and a ski jump with a 69 metre cantilever, to modernist restaurants and recently transformed areas such as Fornebu, the former site of the city's airport. In two introductory essays and more than 150 projects, the book outlines not only how Olso has turned to the water, but also what gives it such a special place in the hearts of architects, designers, and its citizens.
Keywords: Architektur; Oslo; Bildband; Kunstführer